Anna Frangoudaki and Caglar Keyder (eds) Ways to Modernity in Greece and Turkey. Encounters with Europe, 1850-1950. (Library of European Studies 1). - Papagiannopoulos , Kostas (Journal of Greek Archaeology, 2024)
This book is the second volume in the series “Social and Historical Studies on Greece and Turkey,” which aims to provide a platform for dialogue between Greek and Turkish social scientists and historians on “issues of major theoretical importance” that concern the international academic community, by conveying and commenting on experiences from both sides of the Aegean. The first volume explored institutional aspects in the course of nation formation and the emergence of civil society. The second volume delves more into the experiential aspects of this process from the mid-19th century to the mid-20th century. Specifically, this volume focuses on the experience of modernity, the reaction to an unqualified Europeanization perspective, and the convergence through a nationalism-forged “tradition“.